Polyallylamine Hydrochloride-Modified Bovine Serum Albumin Nanoparticles Loaded with α-Solanine for Chemotherapy of Pancreatic Cancer - Wen Z; Luo S; Liu J; Huang Y; Chen G; Cai H (International Journal of Nanomedicine)
Zhengde Wen,1,2,* Shan Luo,2,3,* Juntao Liu,4 Yufan Huang,4 Gang Chen,1 Huajie Cai1 1Department of Surgery, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China; 2Wenzhou Key Laboratory of Perioperative Medicine, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China; 3Department of Anaesthesia, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China; 4Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Huajie Cai; Gang Chen, Email chjwzmu@163.com; qwechen1119@163.comIntroduction: α-Solanine (α-Sol) shows promise for pancreatic cancer (PC) treatment by inhibiting PC cell proliferation, migration, and invasion. However, its clinical application is hindered by poor tumor targeting, significant toxicity, and undesirable pharmacokinetics. To address these issues, this study developed a nanoparticle delivery system (PBSO NPs) using bovine serum albumin as a carrier, with polyallylamine hydrochloride surface modification to enhance α-Sol delivery.Methods: PBSO NPs were characterized using transmission electron microscopy, dynamic light scattering, nanoparticle size analyzers, and Fourier-transform infrared spectroscopy. Their in vitro drug release profile and cellular uptake capabilities were evaluated. Furthermore, in vitro experiments were conducted using mouse pancreatic cancer cells (Panc02) to investigate the effects of PBSO NPs on Panc02 cell viability, migration, invasion, and apoptosis. Additionally, a pancreatic cancer xenograft tumor model was established for in vivo experiments to explore the impact of PBSO NPs on tumor growth.Results: This study successfully developed PBSO NPs with favorable morphology and physiological stability, capable of enhancing cellular uptake. In vitro experiments demonstrated that PBSO NPs significantly inhibited the viability, migration, and invasion of Panc02 cells while promoting apoptosis. Moreover, PBSO NPs enhanced the inhibitory effects of α-Sol on Panc02 cells. In vivo experiments further confirmed that PBSO NPs improved the therapeutic efficacy of α-Sol against PC while partially reducing its toxicity. Additionally, PBSO NPs exhibited good biocompatibility.Discussion: PBSO NPs enhance the therapeutic efficacy of α-Sol against PC by inhibiting the viability, migration, and invasion of PC cells while promoting apoptosis, thereby suppressing the progression of PC. This provides a promising therapeutic strategy for pancreatic cancer treatment.Keywords: pancreatic cancer, α-solanine, bovine serum albumin, polyallylamine hydrochloride, apoptosis